2016
DOI: 10.1080/0886022x.2016.1193873
|View full text |Cite
|
Sign up to set email alerts
|

Serum apelin is associated with affective disorders in peritoneal dialysis patients

Abstract: Objective: Depression and anxiety are prevalent affective disorders in peritoneal dialysis (PD) patients. Recent research has proposed a potential role of apelinergic system in pathogenesis of depression. The present study aimed to evaluate the frequency of depression and anxiety and their potential relation with serum apelin levels among PD patients. Methods: A total of 40 PD patients were enrolled into the study. Depressive symptoms and anxiety were assessed with the Beck's Depression Inventory and the Beck'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
8
2
Order By: Relevance
“…aplnr mRNA has been found in the amygdala, hypothalamus, Ammon's horn, and the dentate gyrus (Lee et al, 2000;Reaux et al, 2001), suggesting a potential role of the apelin/APJ system in emotional behavior. Peritoneal dialysis patients with depression and anxiety had a significantly higher serum apelin than those without depression and anxiety (Oguz et al, 2016).…”
Section: Depression and Anxietymentioning
confidence: 86%
“…aplnr mRNA has been found in the amygdala, hypothalamus, Ammon's horn, and the dentate gyrus (Lee et al, 2000;Reaux et al, 2001), suggesting a potential role of the apelin/APJ system in emotional behavior. Peritoneal dialysis patients with depression and anxiety had a significantly higher serum apelin than those without depression and anxiety (Oguz et al, 2016).…”
Section: Depression and Anxietymentioning
confidence: 86%
“…Three were from East Asia and using a BDI cut of score of >14, they found elevated CRP levels in DS compared to the no DS group 39,40,47 . Three others found the same using a BDI cut-off score of >10 or >13 41,47,48 . All studies using the HAMD or Zung depression scale reported significantly higher CRP levels amongst those with DS 38, 40 44, 46 .…”
Section: Cross-sectional Associations Between Depressive Symptoms (Dsmentioning
confidence: 84%
“…There were 13 studies reporting significant associations between CRP and DS. [38][39][40][41][42][43][44][45][46][47][48][49][50] Eight of these were fit for purpose studies. Three were from East Asia and using a BDI cut of score of >14, they found elevated CRP levels in DS compared to the no DS group 39,40,47 .…”
Section: Cross-sectional Associations Between Depressive Symptoms (Dsmentioning
confidence: 99%
“…However, other studies have shown controversial roles of APLN in psychosis. For example, patients on peritoneal dialysis, who had depression and anxiety, had higher serum apelin levels than those without depression and anxiety (Gok Oguz et al, 2016). Furthermore, apelin-13 exhibited depression-promoting effects in both forced swimming and tail suspension tests (Lv et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A previous meta-analysis has shown that the circulating apelin level is a prominent athero-protective marker against the development of CAD, while the APLNR rs9943582 polymorphism in the APLNR promoter, is associated with an increased risk of CAD (Chen et al, 2017). Furthermore, increased levels of serum apelin have been shown to be significant independent predictors of the development of depression and anxiety in patients on peritoneal dialysis (Gok Oguz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%